DNA Barcoding and Its Applications: A Review - Mampang , Rencellie T.; Auxtero , Karissa Cate A.; Caldito , Carl Jester C.; Abanilla , Jair M.; Santos, Geriell Anne G.; Caipang , Christopher Marlowe A. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
The use of DNA sequences has revolutionized biological classification, specifically through the utilization of the DNA barcode technique, which involves amplifying a standardized DNA fragment for the identification of plant and animal species. The methods and techniques involved in DNA barcoding are introduced and visualized in the paper. As incorporated in various applications in diverse fields, a comprehensive discussion on DNA barcoding is presented, highlighting its relevance and use in species identification and discovery. Furthermore, we explore its different roles, ranging from biodiversity assessment and conservation to food safety, forensic science, biosecurity, and public health. We also introduce the current limitations of the technique and its potential use in future applications of genetics-based discoveries.